Gun culture as domestic technology in the United States: A systematic review - De Cepeda Aparicio, Leyre; Rubira-García, Rainer (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Gun culture is an inherent part of American society as a technology of modern times. For decades, the domestic use of firearms has been consolidated under different political currents, identities, and contexts. The NRA has evolved along with the development of different sociological movements that have normalized guns as a domesticated technology exalting beliefs that are consistent with maintaining their possession despite tragedies suffered. This systematic review aims at evaluating research dealing with gun culture from different perspectives as domestic technology to find avenues of research that help understand the dimensions of gun culture endurance as a core value.